ANALISIS POTENSI SUMBERDAYA LAHAN DESA PAAL MERAH KECAMATAN JAMBI SELATAN SEBAGAI SENTRA PRODUKSI SAYURAN KOTA JAMBI - Busyra Buyung Saidi (Bioplantae, 2013)
Paal Merah Village area consists of two main Landform Group Alluvial and acidic tuff Plain. Alluvial group is small and the widest portion is acidic tuff Plain Group with slopes between 3-8%. Soil types are Typic Endoaquepts area with soil characteristics: moderate depth. Landform regions with acidic tuff little flat plains, soil type Aquic Dystrudepts with moderate depth characteristics, the top layer of somewhat coarse textured, fine sandy, slightly acidic soil pH to neutral, fluffy undercoat, drainage impeded until somewhat hampered, and the pH of acid soils. Region drier types of soil Typic Dystrudepts with soil characteristics: solum deep, well drained, slightly rough texture of the top layer, the bottom layer of smooth, pH acidic to slightly acid soil. While on land rather flat to choppy Kanhapludults Typic soil type, soil characteristics: the depth of the soil solum moderate to deep, well drained, fine texture, and pH of acid soils. Results of the evaluation of land suitability of various agricultural commodities, land can be developed for agricultural commodities featured in the Pal Merah village area of 143 ha (91.7%), while the remaining 23 ha (8.3%) could not be developed for agriculture, because it is a settlement and a service area. Results of the assessment showed that the land unit 1 (Lu-1) that is currently in the form of basin swamp with stagnant swamp grass vegetation is not appropriate (N) for the cultivation of agricultural commodities. Lu 2 and 3 with soil drainage is hampered includes quite fit (S2) for the cultivation of agricultural commodities with a lack of oxygen limiting factors (soil drainage is hampered). Lu 4 including quite fit (S2) by a factor limiting nutrient retention. While Lu 5 in addition to the retention of nutrients for crops also have limiting erosion. Based on the characteristics of the land, then in the plain areas tuff sour flat to choppy very suitable for vegetable crops such as mustard greens, spinach, chilli, egg plant, and leafy vegetable, in the alluvial basin that is now largely overgrown with potential for fisheries. Whereas in choppy lying areas suitable for the cultivation of dry land crops and perennial crops. Key words: Landform, landsuitable, cultivation, soil